Large-Scale Proteome Comparative Analysis of Developing Rhizomes of the Ancient Vascular Plant Equisetum Hyemale - Balbuena, Tiago S.; He, Ruifeng; Salvato, Fernanda; Gang, David R.; Thelen, Jay (Frontiers in Plant Science, 2012)
Equisetum hyemale is a widespread vascular plant species, whose reproduction is mainly dependent on the growth and development of the rhizomes. Due to its key evolutionary position, the identification of factors that could be involved in the existence of the rhizomatous trait may contribute to a better understanding of the role of this underground organ for the successful propagation of this and other plant species. In the present work, we characterized the proteome of E. hyemale rhizomes using a GeLC-MS spectral-counting proteomics strategy. A total of 1,911 and 1,860 non-redundant proteins were identified in the rhizomes apical tip and elongation zone, respectively. Rhizome- characteristic proteins were determined by comparisons of the developing rhizome tissues to developing roots. A total of 87 proteins were found to be up-regulated in both E. hyemale rhizome tissues in relation to developing roots. Hierarchical clustering indicated a vast dynamic range in the expression of the 87 characteristic proteins and revealed, based on the expression profile, the existence of 9 major protein groups. Gene ontology analyses suggested an over-representation of the terms involved in macromolecular and protein biosynthetic processes, gene expression and nucleotide and protein binding functions. Spatial differences analysis between the rhizome apical tip and the elongation zone revealed that only eight proteins were up-regulated in the apical tip including RNA-binding proteins and an acyl carrier protein, as well as a KH-domain protein and a T-complex subunit; while only seven proteins were up-regulated in the elongation zone including phosphomannomutase, galactomannan galactosyltransferase, endoglucanase 10 and 25 and mannose-1-phosphate guanyltransferase subunits alpha and beta. This is the first large scale characterization of the proteome of a plant rhizome. Implications of the findings were discussed in relation to other underground organs and related species.